Long-term maintenance of the mucosal healing induced by azacitidine therapy in a patient with intestinal Behçet's-like disease accompanied with myelodysplastic syndrome involving trisomy 8. Issue 3 (3rd July 2019) - Tanaka, Nahoko; Sakuraba, Hirotake; Hiraga, Hiroto; Mayama, Ko; Kikuchi, Hidezumi; Kishida, Dai; Akemoto, Yui; Hasui, Keisuke; Ota, Shinji; Watanabe, Rina; Murai, Yasuhisa; Maeda, Takato; et al.
Abstract: Myelodysplastic syndromes (MDSs) are a group of myeloid neoplasms characterized by blood cell deformation and dysfunction, and MDS with trisomy 8 is closely linked with intestinal Behçet's-like diseases. Intestinal Behçet's-like disease is refractory to conventional therapies, including prednisolone, immunomodulators, and anti-tumor necrosis factor α agents. Here, we describe a 56-year-old woman with intestinal Behçet's-like disease ascribed to MDS with trisomy 8 who had multiple intractable intestinal ulcers. She presented with periodic fever and abdominal pain. The genetic analysis showed a heterozygous E148Q mutation in the Mediterranean fever gene. The patient did not tolerate treatment with colchicine because of diarrhea; therefore, azacitidine therapy was initiated. One cycle of azacitidine therapy improved the multiple intestinal ulcers, and the periodic fever and abdominal pain gradually disappeared. After eight cycles of azacitidine therapy, ileocolonoscopy, histological assessment and capsule endoscopy revealed mucosal healing. Azacitidine therapy was continued, and mucosal healing was maintained for more than 2 years. This case suggests that azacitidine therapy which has immunoregulatory effects and epigenetic modulations, might control intestinal Behçet's-like disease associated with MDS involving trisomy 8.